Studies on the seasonal abundance of the juveniles of Tenualosa ilisha from Hooghly River estuary of West Bengal, India - Nath, Ashim Kumar; Majhi, Bhuban Mohan (Journal of the Inland Fisheries Society of India, 2019)
The Hooghly-estuarine system harbours important commercial fishes including hilsa, Tenualosa ilisha. Exploitation of hilsa juveniles through fixed bag net and small meshed gill net indicates that they are available in maximum quantity in station 2-Bagbazar region. Pre monsoonal (March-June) catch found in maximum amount than post monsoon (November - February) in all the studied three stations viz. Raichak, Bagbazar and Serampore. Juvenile is noticed throughout the year in station 3-Serampore area. Bag net catch was found maximum in comparison to small meshed gill net in Serampore region. Rainfall, tidal amplitude and salinity has found no effect on their abundance of Hilsa juveniles. Study indicates they are likely to remain there for some time and after attaining 16 cm move deeper region of water.Keywords Hooghly-estuary, Tenualosa ilisha, Juveniles, Bag Net, Gill Net